The Role of Local Government in Registration Agricultural Products as Geographical Indications in Humbahas District - Basaria Tinambunan (CERED Indonesia Institute, 2023)
Geographical indication is the national economic potential which gives commercial value-added on products due to their originality and limitations which cannot be produced in other places. Humbahas Regency which potentially has geographical indication products should register them so that they will not be illegally used by other people and will get legal protection.